IMPLEMENTASI MODEL WATERFALL PADA SISTEM INFORMASI PENJUALAN BERBASIS WEB - Sidik, Sidik; Putri, Wanda; Santoso, Rame (SPEED - Sentra Penelitian Engineering dan Edukasi, 2019)
Abstract - Muslim clothing Sales Information System is an information system that produces a variety of information that could be useful to support sales activities in NB Clothing stores Depok. Data collection system products, product processing, and sales of the products contained in NB Clothing stores still use manual way is to record each and every transaction product data product that happens to be very ineffective. Application Systems generated sales information capable of managing sales data, which includes data items, product processing purchase data in an organized manner. The realization of the development of Muslim clothing sales information system is a web-based application creation that is able to represent information system designed as a wholeKeywords: waterfall model, information system, selling